Clinical Translational Potentials of Stem Cell-Derived Extracellular Vesicles in Type 1 Diabetes - Hu, Wei; Song, Xiang; Yu, Haibo; Sun, Jingyu; Wang, Hongjun; Zhao, Yong (Frontiers in Endocrinology, 2022)
Type 1 diabetes (T1D) is an organ-specific disease characterized by the deficiency of insulin caused by the autoimmune destruction of pancreatic islet β cells. Stem cell-based therapies play essential roles in immunomodulation and tissue regeneration, both of which hold great promise for treating many autoimmune dysfunctions. However, their clinical translational potential has been limited by ethical issues and cell transplant rejections. Exosomes are small extracellular vesicles (EVs) released by almost all types of cells, performing a variety of cell functions through the delivery of their molecular contents such as proteins, DNAs and RNAs. Increasing evidence suggests that stem cell-derived EVs exhibit similar functions as their parent cells, which may represent novel therapeutic agents for the treatment of autoimmune diseases including T1D. In this review, we summarize the current research progresses of stem cell-derived EVs for the treatment of T1D